4CPS-045 Cost effectiveness analysis of meropenem dose optimisation in critical patients. (24th March 2020) - Idoate, AI; Aldaz, A; Aquerreta, I; Ortega, A
Abstract : Background and importance: Meropenem dose adjustment following pharmacokinetic/pharmacodynamic monitoring (TDM) in critical patients (CP) presents a clinical benefit. An economic analysis of this activity could facilitate its use in clinical practice. Aim and objectives: To conduct a cost effectiveness analysis of meropenem TDM in CP versus standard dose (SD) according to the package insert recommendations. Material and methods: We conducted a naturalistic, retrospective, observational cohort study of CP receiving meropenem between May 2011 and December 2017 in a university hospital. Two cohorts were analysed: patients with meropenem TDM (cohort A) and patients with SD meropenem (cohort B). The main effectiveness variable was the percentage of patients with a reduction of at least 80% in the procalcitonin value at the end of meropenem treatment compared with the maximum value during meropenem treatment. Costs included in the analysis were: meropenem, material for drug preparation, TDM, time for preparation, administration and infusion surveillance, meropenem adverse drug reactions (ADR), critical care hospitalisation days and re-entries. Propensity score (PS) matching was applied for patient selection. The χ 2 was used to compare effectiveness and bootstrap to calculate the difference in costs between cohorts. A cost effectiveness analysis with deterministic and probabilistic sensitivity analyses was performed. Results: A total of 154 patients were included (77 per cohort) after PS matching. Meropenem dose was changed in 51 (66.2%) patients with TDM, in most (90.2%) because they were overdosed. In cohort A, 71.4% of patients had reduced procalcitonin by at least 80% compared with 53.2% in cohort B (difference 18.2% (95% CI 3.1; 33.2; p=0.020)). No significant differences were found in ADR between the two cohorts. An average decrease in cost per patient of −1454€ (95% CI −4627;1720€) with TDM was observed, with lower cost per patient for meropenem −62€ (95% CI −116; −4), disposable material −12€ (95% CI −29; 4) and nursing time −38€ (95% CI −71; −4) in cohort A, that offset the TDM cost (47€). Mean hospitalisation cost in patients with TDM was 8912€ versus 10 325€ in cohort B. There was a 75% probability that TDM was more effective and cheaper (dominant) than SD according to the sensitivity analysis. Conclusion and relevance: Meropenem dose adjustment following pharmacokinetic/pharmacodynamic criteria was more effective, with similar safety and lower costs, than dosing according to the package insert recommendations. References and/or acknowledgements: 1. Schuetz P, et al. Procalcitonin-guided antibiotic stewardship. Clin Chem Lab Med 2019. No conflict of interest.